Effect of Er Miao San on peritoneal macrophage polarisation through the miRNA-33/NLRP3 signalling pathway in a rat model of adjuvant arthritis. (31st December 2022) - Liu, Min; Meng, Xiangwen; Xuan, Zihua; Chen, Simeng; Wang, Jin; Chen, Zhiluo; Wang, Jiayu; Jia, Xiaoyi
Abstract: Context: Er Miao San (EMS) is a formulation that contains Atractylodis Rhizoma and Phellodendri Cortex in 1:1 ratio, and is commonly used to treat rheumatoid arthritis (RA) and other inflammatory diseases. Objective: We investigated the mechanism of action and effects of EMS on peritoneal macrophage differentiation in a rat model of adjuvant arthritis (AA). Materials and methods: EMS (3, 1.5 and 0.75 g/kg; once daily) and methotrexate (0.5 mg/kg; once every 3 days) were administered orally from days 21 to 35 after immunisation. Paw swelling and arthritis index were measured; pathological changes in the ankle joint were observed using x-ray and haematoxylin eosin staining. The ratio of CD86/CD206 in macrophages was detected by flow cytometry. Examination of the miRNA-33/NLRP3 signalling pathway was examined by RT-qPCR and western blotting. The levels of cytokines in the serum and cell supernatants were tested by ELISA. Results: EMS significantly reduced the AA index in rats (from 11.0 to 9.3) and pathological changes in the ankle joint (from 3.8 to 1.4). The ratio of CD86/CD206 was reduced, and polarisation to M1 improved (from 0.9 to 0.6) in macrophages of EMS-treated rats. EMS downregulated the miRNA-33/NLRP3 pathway. Furthermore, EMS treatment increased IL-10 and TGF-β levels in the serum and supernatant of macrophages of AA rats and simultaneously decreased the levels of IL-1β and TNF-α. Discussion and conclusions: Our results suggest that EMS may reduce macrophage polarisation to the M1 inflammatory phenotype by downregulating the miRNA-33/NLRP3 pathway in AA rats. These findings may provide new insights into the treatment of RA.